Bentuk Penyajian Gordang Sambilan Pada Upacara Pesta Pernikahan Di Kelurahan Kota Siantar Kecamatan Panyabungan Kota Kabupaten Mandailing Natal - Rafsanjani Rafsanjani; Marzam Marzam (FBS Universitas Negeri Padang, 2021)
This research aims to describe the presentation form of Gordang Sambilan at wedding ceremony in the village of Kota Siantar, Panyabungan Kota district, Mandailing Natal Regency. This research belongs to a qualitative research using descriptive method. The main instrument in this study was the researcher itself and was assisted by supporting instruments such as stationery and cameras. The data were collected through literature study, observation, interview, and documentation. The data were analyzed by describing and concluding the data. The results show that Gordang Sambilan is a traditional art from Mandailing land, North Sumatra, in the form of a mixed tradition ansamble band played by twelve to fourteen male players. Gordang Sambilan is performed on the arena stage where people watching the show surround the group of Gordang Sambilan who are performing. The main musical instrument of this art is Gordang Sambilan which is nine large drums played by being hit by using sticks. In addition, there are other supporting instruments namely ogung, salempong, tali sasayap, saleot, and flute. Gordang Sambilan was once believed to have supernatural or magical power and was used as a medium to ask for help to the spirits of ancestors and jinn on various problems faced by society. In the past, gordang art performances could only be played at Horja Bolon wedding(traditional ceremonies of massive wedding parties). However, nowdays it is freely performed or played serving as entertainment for the People of Mandailing. It can be openly witnessed and performed aiming solely to preserve Mandailing's original culture or art and to keep Gordang Sambilan alive. It is still played and not extinct in the middle of increasingly modern era.